Novel concepts in cervical cancer screening: a comparison of VIA, HPV DNA test and p16INK4a/Ki-67 dual stain cytology in Western Kenya - Orang'o, Omenge; Were, Edwin; Rode, Oliver; Muthoka, Kapten; Byczkowski, Michael; Sartor, Heike; Vanden Broeck, Davy; Schmidt, Dietmar; Reuschenbach, Miriam; Knebel Doeberitz, Magnus von; Bussmann, Hermann (Infectious agents and cancer, 2020)
Screening of unvaccinated women remains essential to mitigate the high morbidity/mortality of cervical cancer. Here, we compared visual inspection with acetic acid (VIA), recommended by WHO as the most cost-effective screening approach in LMICs, with HPV-based screening, and usage of p16INK4a/Ki-67 dual stain cytology.
Gesehen am 11.11.2020